2013
DOI: 10.1039/c3cc44224a
|View full text |Cite
|
Sign up to set email alerts
|

Active ion transporters from readily accessible acyclic octapeptides containing 3-aminobenzoic acid and alanine

Abstract: Ion transporters have been developed from acyclic octapeptides comprising L/D alanine and m-aminobenzoic acid. These octapeptides transport cations up to 3 times faster than their cyclic analog through lipid vesicles. Preliminary CD, XRD and computational studies allude to a 6-9 Å wide tetrameric ion channel as the active ion transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Microscopy studies with peptide 1 also showed that it self-assembles to form nanotubes. 20 The TEM image of octapeptide 2 indicated that it also self-assembles to form bundles of nanotubes (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microscopy studies with peptide 1 also showed that it self-assembles to form nanotubes. 20 The TEM image of octapeptide 2 indicated that it also self-assembles to form bundles of nanotubes (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Octapeptide 1 was synthesized as reported earlier. 20 Peptide 2 was synthesized in solution as outlined in Scheme 1. Peptides 3-5 were also synthesized in solution, following a slightly modified synthetic route.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported octapeptides and amphiphilic tetrapeptides for cation transport (Figure 1b). [ 20 ]…”
Section: Figurementioning
confidence: 99%
“…Anydysfunction in these processes led to various diseases such as cystic fibrosis, Dent disease, Bartter syndrome, and epilepsy [34][35][36][37][38][39][40][41]. In order to mimic the regulatory functions in living systems, a wide range of anion transporters have been investigated that include peptides [42][43][44][45][46][47][48][49][50][51], oligoureas [52][53], anion-π slides [54][55][56][57],steroids [58][59][60][61], calixpyrroles [62][63][64],calixarenes [65][66][67], and other scaffolds [68][69][70]. In particular, peptide based transmembrane anion transporters have attracted great interest.…”
Section: Ion Transport Activitymentioning
confidence: 99%